The reading/writing connection strategies for teaching and learning in the secondary classroom - Olson, Carol Booth (Boston Pearson, 2011)
"The Third Edition features an array of new and updated individual reading/writing strategies, activities and mini-lessons, and it scaffolds these strategies in extended demonstration lessons that teachers can implement in their middle and secondary English classrooms. Well-respected author Carol Booth Olson extends far beyond most books intended for teachers of language arts by integrating reading and writing in creative, theory-based ways. Already a classic in its field, this book intends to explore and reinforce the reading/writing connection and thus help teachers make visible to their students what it is that experienced readers and writers do when they make meaning from and with texts. Lauded by students and professors as a clear and straight-forward book, this new edition includes plenty of material about teaching the writing process and responding to literature, and provides new and improved lessons and activities that help students learn specific strategies. New to this Edition: New demonstration lessons that highlight students showing cognitive strategy use. More high school examples and references to high school texts throughout the book. A focus on 21st century literacies throughout the book with specific activities influenced by the Partnership for 21st Century Skills Framework and the 21st Century English Skills Map. Differentiation activities in several demonstration lessons for different student populations."--Publisher's description.
Chapter 1. What is the reading/writing connection? -- Chapter 2. Introducing students to the cognitive strategies in their mental tool kits -- Chapter 3. Integrating reading and writing instruction through scaffolded demonstration lessons -- Chapter 4. Connecting affect and cognition : creating a community of learners -- Chapter 5. Language arts instruction for mainstream and English language development classrooms : a multiple intelligences approach -- Chapter 6. Strategies for interacting with a text : using reading and writing to learn -- Chapter 7. Teaching literature : from reading to interpretation -- Chapter 8. Reading, thinking, and writing about multicultural literature in culturally diverse classrooms -- Chapter 9. Teaching writing : helps students play the whole range -- Chapter 10. Alternative approaches to the research paper -- Chapter 11. Sharing our responses to texts as readers and writers and revising meaning -- Chapter 12. Correctness can be creative -- Chapter 13. Assessing students' reading and writing in the classroom -- Chapter 14. Cultivating motivated, independent readers and writers through reading and writing workshop.
Keywords: Language arts (Secondary); Language arts (Middle school)